2016
DOI: 10.12660/bre.v99n992016.57454
|View full text |Cite
|
Sign up to set email alerts
|

Measuring the Monetary Policy’s Structural Credibility by the Expected Inflation Determinants: a Kalman Filter Approach for Brazil

Abstract: This paper proposes an extension to Moreira's (2013a,b) approach as a method for measuring the structural credibility of monetary policy under inflation-targeting regimes using the main determinants of expected inflation and Kalman filtering with calibration parameters. Such a method is exempted from some of the restrictions found in existing credibility indexes, such as in Cecchetti and Krause (2002). The proposed approach was applied to the Brazilian case as an illustration and yielded robust results, demons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 22 publications
1
3
0
1
Order By: Relevance
“…Finally, our work contributes to the international literature on inflation targeting regimes as it converges to previous evidence and intuition such as in Baxa et al (2015), Mishkin and Schimidt-Hebel (2007), Benati (2008) and Moreira (2016). That is, although the adoption of an inflation target can be accompanied by improvements in inflation dynamics over time, the true factors determining or at least conditioning such an outcome could be beyond the choice of a specific nominal anchor.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…Finally, our work contributes to the international literature on inflation targeting regimes as it converges to previous evidence and intuition such as in Baxa et al (2015), Mishkin and Schimidt-Hebel (2007), Benati (2008) and Moreira (2016). That is, although the adoption of an inflation target can be accompanied by improvements in inflation dynamics over time, the true factors determining or at least conditioning such an outcome could be beyond the choice of a specific nominal anchor.…”
Section: Discussionsupporting
confidence: 79%
“…That is, although the adoption of an inflation target can be accompanied by improvements in inflation dynamics over time, the true factors determining or at least conditioning such an outcome could be beyond the choice of a specific nominal anchor. Constraints relating to monetary and fiscal policies' credibility are an important condition (Benati, 2008;Moreira, 2016). In our study, the evidence for a deterioration of the inflation deviation dynamics since 2010, in Brazil, can be associated with a social loss in terms of an increase of the public debt to GDP ratio and the public's general perception of less efficiency in the conduction of the economic policy during President Dilma Rousseff's mandate.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…By analyzing the stylized facts highlighted above, this paper sought to broaden and collaborate to the debate about monetary policy in Brazil in recent years, such as in De Mendonça and Faria (2011) and Moreira (2013Moreira ( , 2016. For future work, it is suggested that other methods, such as , be used to find other relationships between the selected variables.…”
Section: Discussionmentioning
confidence: 99%
“…12. A lista é extensa e inclui Perry (1983), Blanchard (1984), Cukierman e Meltzer (1986), Svensson (1993), Bomfim e Rudebusch (2000), Cecchetti e Krause (2002), Laxton e N'Diaye (2002), Johnson (1998;2002), Clarida e Waldman (2007) Na literatura brasileira, a referida ferramenta é usada em Teles e Nemoto (2005), que estimam o modelo de Lucas (1973) para mensurar a magnitude do trade-off entre inflação e produto no Brasil; Nogueira (2009), que adota a mesma metodologia para dados de inflação e produto de Suécia, Reino Unido, Brasil e México; e Moreira (2016), que propõe uma equação baseada na curva de Phillips para as expectativas da inflação acumulada nos doze meses seguintes e a estimam, levando em conta que: i) o impacto da inflação passada pode mudar ao longo do tempo; e ii) que o coeficiente que mede esse impacto funciona como uma medida de credibilidade das autoridades monetárias.…”
Section: Uma Breve Revisão Da Literaturaunclassified